Revealing Gender Dynamics: Comparative Analysis of Religiosity, Emotional Intelligence, and Academic Resilience in Junior High School Students - Herdiansyah, Diki; Fauziah, Mufied; Kawai, Norimune; Kumara, Agus Ria; Suci Rohmadheny, Prima; Muyana, Siti (Pusat Studi gender dan Anak (PSGA) Universitas Islam Negeri Walisongo Semarang, 2024)
In ever-developing social dynamics, understanding gender roles is becoming increasingly important. Previous research suggests that gender can influence how individuals respond to academic and emotional challenges, with factors such as religiosity and emotional intelligence playing an important role in this process. This study investigated gender differences in religiosity, emotional intelligence, and academic resilience among students aged 12–16 years. The method used is comparative quantitative. A total of 626 students (286 males and 340 females) were selected through simple random sampling. The data collection instruments used are the religiosity scale, emotional intelligence scale, and academic resilience scale, developed independently by the researcher and tested for validity and reliability. Data analysis uses the independent sample t-test. The results of data analysis on the religiosity variable show that there is a difference of 0.000 < 0.05 in the religiosity of male and female students. In contrast, the emotional intelligence and academic resilience variables show that there is a difference in emotional intelligence of 0.145 > 0.05 and academic resilience of 0.203 > 0.05 in boys and girls. Overall, the results of this analysis provide important insights into the influence of gender on several aspects of student psychology and behavior. These results can be used to design more inclusive and gender-sensitive educational policies and programs, as well as support the holistic personal development of all individuals, regardless of gender.